2013
DOI: 10.1063/1.4805005
|View full text |Cite
|
Sign up to set email alerts
|

Probing embedded structural inhomogeneities in MgZnO alloys via selective resonant Raman scattering

Abstract: The issue of phase segregation, inherent to the MgZnO alloy system, was investigated via selective resonant Raman scattering. We demonstrate that it is a highly sensitive technique for the detection of embedded structural inhomogeneities. MgZnO thin-films with bandgaps that span the UV-range of 3.2–5.7 eV were realized. Under resonant conditions facilitated via different laser excitation energies, the LO-phonon behavior indicated that the phase segregation is in the range of 35%–65% Mg, in which domains of hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…As commented before, previous optical absorption spectroscopy studies [15,17] tration a low-energy absorption tail appears overlapping to the main absorption edge of the sample. In Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…As commented before, previous optical absorption spectroscopy studies [15,17] tration a low-energy absorption tail appears overlapping to the main absorption edge of the sample. In Fig.…”
Section: Resultsmentioning
confidence: 77%
“…However, the study of the optical properties of Mg x Zn 1−x O thin films with phase separation has been scarce [15][16][17]. Those previous studies find with optical absorption spectroscopy [15,17] a lowenergy absorption tail overlapped to the main absorption edge for Mg concentrations above a critical concentration when phase separation occurs. The origin of this absorption tail observed in Mg x Zn 1−x O thin films grown by different methods, has been tentatively explained by some authors [17] as due to the beginning of the absorption edge of the coexisting rock-salt phase.…”
Section: Introductionmentioning
confidence: 99%
“…This band-edge for the alloys can be explained in terms of in-gap density of states due to structural and morphology defects as well as alloy inhomogeneities [20,21]. We previously found that the derivative method yields a good measure of the alloy's bandgap; sometime referred to as the optical gap rather than the fundamental gap [19]. The energies of the optical gaps are usually somewhat lower than those of the fundamental gaps.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 1 and 2a, b present the XRD and the transmission spectra, respectively, of the Mg 0.17 Zn 0.83 O and Mg 0.34 Zn 0.66 O samples. The bandgaps were estimated via the transmission derivative method, dT/dE, that was shown to be a useful approach for ascertaining bandgaps of alloys [19], and in particular provides a suitable definition of bandgap for the alloys studied in this paper. Usually, the transmission spectrum of the alloy is not decreasing in a sharp manner at the spectral-range of the bandgap, but rather exhibits an Urbach-type band-edge tailing.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of ZnO is hexagonal wurtzite, while that of MgO is cubic rocksalt. The different crystal structure of the two end-members impedes the realization of a complete solid-solution, of the Mg x Zn 1-x O alloy system [11,12]. Achieving good solubility depends generally on the growth techniques and on post-growth treatments such as annealing.…”
Section: Introductionmentioning
confidence: 99%